Long working hours and health in Denmark: a post hoc analysis of three cohort studies - Harald Hannerz (BMC, 2024)
Abstract Background To protect the safety and health of workers, national legislations often stipulate an upper limit to weekly working time. The purpose of the present study was to provide information that may facilitate the obtainment of evidence-based limits to weekly working time. Objective To estimate incidence rate ratios (RRs) of (i) hospital treatment or death due to accidental injuries, (ii) redeemed prescriptions for psychotropic drugs and (iii) redeemed prescriptions for antihypertensive drugs, respectively, as continuous functions of weekly working hours among employees in the general population of Denmark. Methods Baseline data on working time arrangements were obtained from the Danish Labor Force Surveys of 1999-2013. Follow-ups with a mean duration of 1.8, 4.0 and 6.6 years for accidental injuries, psychotropic drugs and antihypertensive drugs, respectively, were accomplished through national registers. Adjusted RRs were obtained through Poisson regression in the interval 32-80 weekly working hours (wwh). The reference (standard working hours) was set at 37 wwh. RR estimates were interpreted in accordance with a modified version of Monson's guide to strength of associations, in which a RR in the open interval 0.83 to 1.2 is classified as 'no association' (too weak to be detected by observational studies). Results The estimated RRs as well as the upper and lower limits of their 95% confidence intervals lied within the no-association zone throughout the intervals 32-76, 32-64 and 32-69 wwh, for accidental injury, psychotropic drug use and antihypertensive drug use, respectively. The estimated RRs for psychotropic drug use decreased from 1.08 (95% CI: 1.03-1.13) at 32 wwh to 0.96 (0.93-0.99) at 45 wwh. They thereafter increased to 1.00 (0.95-1.06) at 55 wwh and 1.31 (1.08-1.63) at 80 wwh. The estimated RRs for accidental injury and antihypertensive drug use increased slowly from 1.00 at 37 wwh to 1.04 (0.88-1.24) and 1.11 (0.94-1.31), respectively, at 80 wwh. Conclusion These results suggest that, from a societal perspective, the effect of wwh on the rates of these types of morbidity is negligible throughout the interval 32-64 wwh.